1988
DOI: 10.1042/bj2500343
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of calcium-dependent phospholipase A2 activity in membrane preparation of rabbit neutrophils. Absence of activation by fMet-Leu-Phe, phorbol 12-myristate 13-acetate and A-kinase

Abstract: The presence of a phospholipase A2 (PLA2) activity in rabbit neutrophil membrane preparation that is able to release [1-14C]oleic acid from labelled Escherichia coli has been demonstrated. The activity is critically dependent on the free calcium concentration and marginally stimulated by GTP gamma S. More than 80% of maximal activity is reached at 10 microM-Ca2+. The chemotactic factor, fMet-Leu-Phe, does not stimulate the PLA2 activity in this membrane preparation. Pretreatment of the membrane preparation, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
20
1

Year Published

1989
1989
1996
1996

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 22 publications
5
20
1
Order By: Relevance
“…Thus, some effects of TPA were suggested to result from direct membrane perturba tion, but not the activation of protein kinase C (13,14). In contrast, our results indicate that TPA-induced enhance ment of catecholamine secretion in digitonin-permeabil ized adrenal medullary cells is due to the activation of protein kinase C. The concentration of calphostin C used in the present study is higher than that reported in the in vitro experiment (9).…”
Section: Nicotiniccontrasting
confidence: 55%
See 1 more Smart Citation
“…Thus, some effects of TPA were suggested to result from direct membrane perturba tion, but not the activation of protein kinase C (13,14). In contrast, our results indicate that TPA-induced enhance ment of catecholamine secretion in digitonin-permeabil ized adrenal medullary cells is due to the activation of protein kinase C. The concentration of calphostin C used in the present study is higher than that reported in the in vitro experiment (9).…”
Section: Nicotiniccontrasting
confidence: 55%
“…H-7, a protein kinase C inhibitor, has been reported to fail to inhibit TPA-induced enhancement of [3H]-arachi donic acid release caused by the Ca2+ ionophore A23187 in rabbit neutrophils (13,14). Thus, some effects of TPA were suggested to result from direct membrane perturba tion, but not the activation of protein kinase C (13,14).…”
Section: Nicotinicmentioning
confidence: 99%
“…Cyto- solic and secretory PLA2s have been described in a number of cells, including neutrophils (Traynor & Authi, 1981;Balsinde et al, 1988;Ramesha & Ives, 1993), monocytes (Wightman et al, 1981;Ulevitch et al, 1988;Clark et al, 1990) and platelets (Matsumoto et al, 1988;Kramer et al, 1989;Takayama et al, 1991). PLA2 enzymes may be involved in cell proliferation and signal transduction as well as in the pathogenesis of disease processes such as inflammation (Mukherjee et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that PMA produces its effect in part by direct membrane perturbation. A similar idea has been advanced for the potentiating effect of PMA on stimulated arachidonic acid release (22,23).…”
Section: Discussionmentioning
confidence: 93%